2021
DOI: 10.1002/pssr.202100409
|View full text |Cite
|
Sign up to set email alerts
|

Functional Modifications Induced via X‐ray Nanopatterning in TiO2 Rutile Single Crystals

Abstract: The possibility to directly write electrically conducting channels in a desired position in rutile TiO2 devices equipped with asymmetric electrodes—like in memristive devices—by means of the X‐ray nanopatterning (XNP) technique (i.e., intense, localized irradiation exploiting an X‐ray nanobeam) is investigated. Device characterization is carried out by means of a multitechnique approach involving X‐ray fluorescence (XRF), X‐ray excited optical luminescence (XEOL), electrical transport, and atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…5B) an increase in the surface conductivity of the TiO 2 crystal, which is more evident in the borders of the bump. A previous study 10 using space-resolved X-ray excited optical luminescence (XEOL) showed that these higher conductivity regions are associated with a lower intensity of a XEOL signal centered at 830 nm, which is attributed to the radiative recombination of electrons trapped in intra-band gap states with free holes in the valence band. 36 These states have been ascribed to the presence of lattice defects like V O or Ti interstitials.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…5B) an increase in the surface conductivity of the TiO 2 crystal, which is more evident in the borders of the bump. A previous study 10 using space-resolved X-ray excited optical luminescence (XEOL) showed that these higher conductivity regions are associated with a lower intensity of a XEOL signal centered at 830 nm, which is attributed to the radiative recombination of electrons trapped in intra-band gap states with free holes in the valence band. 36 These states have been ascribed to the presence of lattice defects like V O or Ti interstitials.…”
Section: Resultsmentioning
confidence: 97%
“…[6][7][8] Then, the process was extended to oxides with tightly bound oxygen atoms, like TiO 2 , where the creation of X-ray-induced V O led to a local increase of the material electrical conductivity. 9,10 The possibility to manipulate the oxygen content at the nanoscale by XNP could be extremely interesting for the fabrication of oxide-based electronic devices, such as memristors. Memristive devices, which can retain a state of internal resistance based on the history of applied voltage and current, are attracting increasing interest for several applications ranging from nonvolatile memories to neuromorphic computing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation